2015
DOI: 10.1016/j.bone.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A distinct regulatory region of the Bmp5 locus activates gene expression following adult bone fracture or soft tissue injury

Abstract: Bone morphogenetic proteins (BMPs) are key signaling molecules required for normal development of bones and other tissues. Previous studies have shown that null mutations in the mouse Bmp5 gene alter the size, shape and number of multiple bone and cartilage structures during development. Bmp5 mutations also delay healing of rib fractures in adult mutants, suggesting that the same signals used to pattern embryonic bone and cartilage are also reused during skeletal regeneration and repair. Despite intense intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 95 publications
1
36
0
Order By: Relevance
“…Recently, a ~18 kb region of the murine Bmp5 locus was reported to activate expression from minimal promoters in injury contexts 33 , suggesting it may harbor a TREE analogous to the LEN element we describe here. We suspect that diverse classes of TREEs exist, including elements activated during development and re-activated by injury 34 or during regeneration, elements that activate expression preferentially during regeneration in multiple tissues, and regeneration-specific elements that are more tissue-restricted.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, a ~18 kb region of the murine Bmp5 locus was reported to activate expression from minimal promoters in injury contexts 33 , suggesting it may harbor a TREE analogous to the LEN element we describe here. We suspect that diverse classes of TREEs exist, including elements activated during development and re-activated by injury 34 or during regeneration, elements that activate expression preferentially during regeneration in multiple tissues, and regeneration-specific elements that are more tissue-restricted.…”
Section: Discussionmentioning
confidence: 64%
“…This study provides a molecular basis to explain how some epicardial genes that are transcriptionally activated during embryonic development can be re-induced after injuries; that is, by sharing regulatory sequences. Similarly, by deleting different genomic regions surrounding mouse Bmp5, essential for skeletal development and bone repair, Guenther et al identified separable genomic regions responsible for Bmp5 expression in discrete anatomic domains during normal development or following injuries (38). Intriguingly, the 18-kb injury-responsive region is sufficient to trigger gene expression in mesenchymal or epithelial cells in multiple tissues, suggesting it might contain an injury-responsive enhancer element.…”
Section: Early Signals For Regenerationmentioning
confidence: 99%
“…These sequences, in combination with a minimal promoter, were sufficient to direct and maintain expression of a transgenic reporter or even a potent mitogen in regeneration settings but not in uninjured adult tissue. Together, these studies and others, like those identifying injury-responsive sequences near the murine BMP5 gene or chromatin regions that are modulated by exposure to inflammation in murine skin epithelial stem cells (Guenther et al, 2015; Naik et al, 2017), indicate that there may exist thousands of cis -regulatory elements that activate gene expression after tissue injury or stress, and/or during regeneration. Elements like these provide ways researchers can further probe gene function during regeneration through their inherent ability to turn on and off in response to injury and regeneration (Kang et al, 2016).…”
Section: Finding Triggers and Brakes For Regenerationmentioning
confidence: 79%
“…Images in (B) are adapted from Kang et al, 2016. Images in (C) are adapted from Guenther et al, 2015. Image in (D) is adapted from Liu et al, 2017.…”
Section: Figurementioning
confidence: 99%